2013
DOI: 10.1097/mbc.0b013e32835d53ec
|View full text |Cite
|
Sign up to set email alerts
|

Can divergent plasmin–antiplasmin–carbon monoxide interactions in young, healthy tobacco smokers explain the ‘smokerʼs paradox’?

Abstract: In the setting of acute myocardial infarction, decreases in early/late mortality, reocclusion after thrombolysis, and restenosis rate after percutaneous intervention are lower in smokers - this phenomenon has been designated as the 'smoker's paradox'. These benefits of smoking, however, are abrogated by stent placement. We hypothesized that fibrinolytic vulnerability would change in response to smoking, and that inhaled carbon monoxide may play a role. Smoking patients (n = 20, two cigarettes consumed within 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Smoking has been associated with increased hematocrit, platelet activation and aggregation, vasoconstriction, increased circulating levels of fibrinogen, thrombin generation, impaired endogenous fibrinolytic capacity, and increased response to clopidogrel. 7,[35][36][37][38] As a result, the pathogenesis of vascular occlusions in smokers may be more because of changes in thrombogenicity than in atherosclerotic plaque rupture or morphology. This may be particularly true in those patients with fewer clinically manifest traditional atherosclerosis risk factors, whereas in nonsmokers, occlusion may be more frequently because of rupture or ulceration of atheromatous plaque with formation of platelet-rich clot.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been associated with increased hematocrit, platelet activation and aggregation, vasoconstriction, increased circulating levels of fibrinogen, thrombin generation, impaired endogenous fibrinolytic capacity, and increased response to clopidogrel. 7,[35][36][37][38] As a result, the pathogenesis of vascular occlusions in smokers may be more because of changes in thrombogenicity than in atherosclerotic plaque rupture or morphology. This may be particularly true in those patients with fewer clinically manifest traditional atherosclerosis risk factors, whereas in nonsmokers, occlusion may be more frequently because of rupture or ulceration of atheromatous plaque with formation of platelet-rich clot.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations include higher incidence of right coronary artery involvement and non-anterior wall MI, with potentially less incidence of life threatening ventricular arrhythmias and LV systolic dysfunction compared with LAD involvement and anterior wall MI. Moreover, smokers have a higher incidence of hypercoagulable state than non-smokers and this may lead to acute coronary thrombosis in the presence of less severe atherosclerosis thus predicting a better response to thrombolytic therapy [25]. Registries and clinical studies have found a significantly lower in-hospital mortality in acute MI and NSTEACS among smokers than non-smokers [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, one sample of plasma underwent analyses to determine fibrinolytic vulnerability with the addition of tissue-type plasminogen activator (tPA). Its sample consisted of 316 ml of plasma; 10 ml of TF reagent (0.1% final concentration in dH 2 O); 10 ml tPA (580 U/mg; Genentech, Inc., San Francisco, California, USA), diluted with 50 mmol/l potassium phosphate buffer (pH 7.4), for a final activity of 100 U/ml; 3.6 ml of dH 2 O; and 20 ml of 200 mmol/l CaCl 2 as per our previously described assay [12]. Data were collected for this sample until clot lysis time was observed.…”
Section: Case Reportmentioning
confidence: 99%